Role of N-terminal pro-B-type natriuretic peptide in predicting mortality in heart failure - Kamal Kant Jena; N Vishwanathan; G Manohar; Prashant Kumar Singh; Nayan Chakraborty (Journal of Clinical and Preventive Cardiology, 2021)
Background: N-terminal pro-B-type natriuretic peptide (NT-proBNP) improves emergency room diagnosis and is a prognostic marker of acutely decompensated heart failure (HF) after hospitalization. We tried to assess the prognosis in heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF) using the biomarker. Methods: Patients were categorized into HFpEF (left ventricular ejection fraction [LVEF] ≥50%) (n = 102), HF with midrange EF (LVEF of 40%–49%) (n = 106), and HFrEF (LVEF ≤40%) (n = 112) as per the ESC classification of HF subtypes. Prognosis by absolute and percentage change in NT-proBNP at admission and at the 10th day of treatment was found in 3-month follow-up. Mortality after discharge was also assessed. Results: Among all HF groups, a reduction of NT-proBNP <20% at 10 days predicted mortality, hazard ratio (HR) – 14.9 (95% confidence interval [CI]: 3.8–57.9), P = 0.0001. The risk of mortality in HF patients with NT-proBNP reduction of <20% in 10 days was 14.9 times higher in 3-month follow-up. NT-proBNP more than 12,000 pg/mL at admission had a mortality risk of 23.3% in the HFrEF group, HR – 23.45 (95% CI: 2.9–189.4), P = 0.003. NT-proBNP on the 10th day, more than 9000 pg/mL, had a mortality risk of 21.4% in the HFrEF group, HR – 23.3 (95% CI: 4.9–110.5), P = 0.001. Conclusion: NT-proBNP proved to be a superior modality in finding out prognosis in HF. Patients with the HFrEF group had a higher mortality in our study. Comorbidities play an important role in affecting the prognosis in patients with HFpEF with lower NT-proBNP.